Visible Near Infrared (Vis-Nir) Spectroscopy For Quantification Of Hela And Du145 Cells - Sudik, Suhainah (2020)
The most common diagnostic techniques for cancer include ionizing testing such as imaging techniques require significant financial resources and infrastructure, which limit access to these modalities. In contrast, optical spectroscopy is non-ionizing testing that has shown promising potential as additional tools for cancer diagnosis, one of it through exhibiting the ability to display distinctive spectral characteristics between normal and cancerous tissues. In this study, the visible and near-infrared, VIS–NIR (400-1100 nm) absorbance spectroscopy measurement with and without phenol red cultured media of cervical cancer (HeLa) and prostate cancer (DU145) cell lines was used through cell culturing technique.